Deloitte South Africa : complicit, conniving or caught unawares? - Sieff, Grant; Bowen, Amanda (London : Wits Business School, 2021)
By March 2021, two years had passed since Deloitte South Africa (SA) had released its Transparency Report which detailed its journey of self-reflection as a firm and the ways in which it intended to rebuild trust and restore professionalism. Since 2017, the firm had lost R3 billion ($204 million) in revenue, and suffered significant reputational damage, after being caught up in several scandals involving corruption and unethical conduct. The report detailed the progress the firm had made in rebuilding itself, enhancing the quality of its work and restoring good governance. Had Deloitte SA done enough to acknowledge and rectify its ethical and governance lapses, and restore trust?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business ethics; Transparency in government -- South Africa